Internal Versus External Sources of Plasma at Saturn: Overview From Magnetospheric Imaging Investigation/Charge‐Energy‐Mass Spectrometer Data. Issue 6 (15th June 2018) - Allen, R. C.; Mitchell, D. G.; Paranicas, C. P.; Hamilton, D. C.; Clark, G.; Rymer, A. M.; Vines, S. K.; Roelof, E. C.; Krimigis, S. M.; Vandegriff, J.
Abstract: Plasma composition observations provide a useful mechanism for investigating plasma sources and subsequent evolution within planetary magnetospheres. While He ++ is the second most abundant ion species in the solar wind, there are no known sources of He ++ ions within the magnetosphere of Saturn, allowing He ++ to serve as a tracer of solar wind ions within the Kronian magnetosphere. Meanwhile, water group ions (W +, consisting of O +, OH +, H2 O +, and H3 O + ) and H2 +, known to originate within the magnetosphere of Saturn, serve as a tracer of internally ionized plasma. In this paper, we investigate the relative abundances and properties of energetic (32–220 keV) ion species originating from sources within the magnetosphere and from the solar wind. Solar wind‐originating ions are observed to have significant relative abundance (up to ~0.05) in the midnight, dawn, and noon local time quadrants at high radial distances (~40, ~45, and ~20 RS, respectively). Several possible entry processes, such as reconnection and Kelvin‐Helmholtz instabilities, are outlined in this paper as well as a discussion of subsequent transport. Plain Language Summary: While the sources of plasma within the magnetosphere of Saturn have long focused on internal generation, this study seeks to estimate the amount of plasma entering into the magnetosphere from the solar wind. Using a mission averaged vantage point of the global relative abundances of 32 to 220 keV ions, the internal to external plasma is investigated in order to estimate the relative amount of solar wind‐originating ions within the magnetosphere of Saturn, as well as the regions of their importance. Solar wind‐originating ions are predominantly seen within the midnight and dawn quadrants of Saturn, while the dayside and inner magnetosphere is dominated by internally generated plasma. The energetic plasma is also seen to peak in density near a radial distance of 10 RS as a consequence of loss processes closer to the planet and radial diffusion further from Saturn. Key Points: Energetic (32‐220 keV) H +, H2 +, He +, He ++, and W + densities are used to investigate internal versus external plasma sources Energetic solar wind He ++ observed in the magnetotail suggest access through Kelvin‐Helmholtz Instabilities and reconnection processes Both internally and externally generated plasma species observe a peak in density at a radial distance of ~10 RS